Multidisciplinary views on discourse genre : a research agenda - Stukker, Ninne Maria, 1971-; Bateman, John A.; McNamara, Danielle S.; Spooren, Wilbert (Routledge, 2024)
This collection sets out an innovative research agenda for advancing a multidisciplinary approach to genre, bringing together researchers from a variety of disciplines to enhance our existing understanding of the challenges and opportunities for current and future genre research. The volume brings together perspectives from across disciplinary borders, including such fields as discourse studies, cognitive studies, computational discourse analysis, and education, to advance genre research into new directions, as it has historically been studied from a mono-disciplinary perspective. The book highlights how fruitful a multidisciplinary approach can be in accounting for the dynamic complexity of the discourse genres that underpin daily life, exploring six broad themes: defining genre; stability and variation; genre and cognition; computational methods; language and literacy development; and genre education. Taken together, the volume makes the case for the value of such an approach in better accounting for the conceptual and empirical complexities of genre and, in turn, serving as a springboard for innovations in genre research.This book will be of interest to students and scholars in linguistics, discourse studies, discourse psychology, media studies, language and literacy development, and education.
Keywords: Discourse analysis.; Language and languages -- Style.; Discourse markers.; elektronické knihy; electronic books